2014
DOI: 10.1038/nature13994
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer–core-promoter specificity separates developmental and housekeeping gene regulation

Abstract: Gene transcription in animals involves the assembly of RNA polymerase II at core promoters and its cell-type-specific activation by enhancers that can be located more distally. However, how ubiquitous expression of housekeeping genes is achieved has been less clear. In particular, it is unknown whether ubiquitously active enhancers exist and how developmental and housekeeping gene regulation is separated. An attractive hypothesis is that different core promoters might exhibit an intrinsic specificity to certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

46
473
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(537 citation statements)
references
References 44 publications
(72 reference statements)
46
473
7
Order By: Relevance
“…How does each enhancer find its target? Proximity to one vs. anther promoter helps, but there are numerous exceptions, and open questions remain in spite of recent progress such as the finding that Drosophila 'housekeeping' genes specifically interact with an enhancer class of their own (Zabidi et al, 2014). One also may wonder, why remote control?…”
Section: Why Activation Over Long Distances?mentioning
confidence: 99%
“…How does each enhancer find its target? Proximity to one vs. anther promoter helps, but there are numerous exceptions, and open questions remain in spite of recent progress such as the finding that Drosophila 'housekeeping' genes specifically interact with an enhancer class of their own (Zabidi et al, 2014). One also may wonder, why remote control?…”
Section: Why Activation Over Long Distances?mentioning
confidence: 99%
“…For instance, it was shown that the presence of specific core promoter elements in Drosophila makes promoters responsive to distinct enhancers [119]. A recent functional study of enhancer activity genome-wide revealed specificity of enhancers towards either housekeeping or developmental core promoters that differ in their core promoter elements, separating two major transcriptional programs in Drosophila [14].…”
Section: Diverse Promoter Architectures Enable Complex Regulatory Lanmentioning
confidence: 99%
“…Interestingly, the distinct promoter classes were recently shown to respond to regulation by different sets of distal-acting enhancers, separating the housekeeping and developmental transcriptional programs in Drosophila [14] and emphasizing the importance of core promoters in transcriptional regulation during development.…”
Section: Promoter Classes and Modes Of Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…They have multiple, functionally distinct 1 and sometimes physically overlapping 2 architectures, which determine their responsiveness to long-range regulation and to developmental and differentiation regulatory programs (reviewed in ref. 3).…”
mentioning
confidence: 99%